Pu-241 and Pu-241/Pu239+240 activity ratio in environmental samples from Finland as evaluated by the ingrowth of Am-241 - Salminen-Paatero, Susanna; Paatero, Jussi; Jaakkola, Timo (Finnish Environment Institute, 2016)
Peer reviewed